PENGARUH HARGA, GAYA HIDUP, CITRA MEREK, TERHADAP LOYALITAS MEREK DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING DI JANJI JIWA KUDUS - Fifi Sofiatul Karimah; Eldes Willy Filatrovi (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aims to determine the effect of price, lifestyle, brand image on brand loyalty with purchase decisions as intervening variables in Janji Jiwa Kudus. The population in this study are Janji Jiwa consumers who live in Kudus. The sample used in this study was 100 respondents. The analytical tool used is AMOS 24 software. The results of testing in this study can be concluded that (1) Price has no effect on purchasing decisions, (2) Lifestyle has no effect on purchasing decisions, (3) Brand image has an effect on purchasing decisions, (4) ) Price has no effect on brand loyalty, (5) Lifestyle has no effect on brand loyalty, (6) Brand image has no effect on brand loyalty and (7) Purchase decision has no effect on brand loyalty. Keywords: Price, Lifestyle, Brand Image, Purchase Decision, Brand Loyalty.